2023
DOI: 10.1186/s40478-023-01506-z
|View full text |Cite
|
Sign up to set email alerts
|

Clinico-pathological and epigenetic heterogeneity of diffuse gliomas with FGFR3::TACC3 fusion

Abstract: Background Gliomas with FGFR3::TACC3 fusion mainly occur in adults, display pathological features of glioblastomas (GB) and are usually classified as glioblastoma, IDH-wildtype. However, cases demonstrating pathological features of low-grade glioma (LGG) lead to difficulties in classification and clinical management. We report a series of 8 GB and 14 LGG with FGFR3:TACC3 fusion in order to better characterize them. Methods Centralized pathological … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(22 citation statements)
references
References 38 publications
0
21
0
1
Order By: Relevance
“…264 Similarly, a newly identified splicing mutant, FGFR3Δ7-9, which directly connects exon 6 and exon 10, directly phosphorylates the ten-eleven translocation-2 DNA demethylase and causes its ubiquitinated degradation, activating the AKT pathway to promote the proliferation of HCC. 125,265 FGFR3 may also undergo rearrangements or amplifications in gliomas 266,267 and lung cancer. 268,269 In glioma, the most common fusion partner of FGFR3 is TACC3, and the fusion process of FGFR3-TACC3, which requires HSP90, requires the involvement of cell division cycle 37 (CDC37).…”
Section: Fgfr3 Functions As a Promoter In Tumorsmentioning
confidence: 99%
See 1 more Smart Citation
“…264 Similarly, a newly identified splicing mutant, FGFR3Δ7-9, which directly connects exon 6 and exon 10, directly phosphorylates the ten-eleven translocation-2 DNA demethylase and causes its ubiquitinated degradation, activating the AKT pathway to promote the proliferation of HCC. 125,265 FGFR3 may also undergo rearrangements or amplifications in gliomas 266,267 and lung cancer. 268,269 In glioma, the most common fusion partner of FGFR3 is TACC3, and the fusion process of FGFR3-TACC3, which requires HSP90, requires the involvement of cell division cycle 37 (CDC37).…”
Section: Fgfr3 Functions As a Promoter In Tumorsmentioning
confidence: 99%
“…FGFR3 may also undergo rearrangements or amplifications in gliomas 266,267 and lung cancer 268,269 . In glioma, the most common fusion partner of FGFR3 is TACC3, and the fusion process of FGFR3–TACC3, which requires HSP90, requires the involvement of cell division cycle 37 (CDC37) 270 .…”
Section: Fgfr Is Involved In Human Tumorsmentioning
confidence: 99%
“…Diffuse gliomas with FGFR3:TACC3 fusion do not represent a distinct nosological entity in the 2021 WHO classification of CNS tumors. Most reported cases had a high‐grade morphology, consisting of microvascular proliferation and necrosis [ 1 , 2 ] and were considered to represent a subgroup of IDH wild‐type GBMs distinguished by prolonged overall survival. Within the minor proportion of diffuse gliomas with FGFR3::TACC3 fusion that lack histological signs of malignancy, some cases are also devoid of the molecular features of GBMs, whereas others have chromosomes 7 gain/10 loss and/or pTERT mutation [ 1 , 2 ], which supports a diagnosis of GBM, IDH ‐wildtype, according to the 2021 WHO CNS classification, as in the present case.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that these tumors may represent precursors of GBM or undersampled GBMs. Two studies have shown that the majority exhibit a distinct DNA methylation profile [ 1 , 2 ]. Indeed, of 27 histologically diffuse low‐grade gliomas with FGFR3::TACC3 fusion and pTERT mutation and/or chromosomes 7 gain/10 loss, only five cases had a calibration score above 0.90 for the methylation class “GBM IDH‐wildtype” using the 11b4 version of the Heidelberg classifier [ 1 , 2 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation